Fibroblast‐specific IL11 signaling drives chronic inflammation in murine fibrotic lung disease. Issue 9 (12th July 2020) - Ng, Benjamin; Dong, Jinrui; Viswanathan, Sivakumar; Widjaja, Anissa A.; Paleja, Bhairav S.; Adami, Eleonora; Ko, Nicole S. J.; Wang, Mao; Lim, Stella; Tan, Jessie; Chothani, Sonia P.; Albani, Salvatore; et al.
Abstract: Repetitive pulmonary injury causes fibrosis and inflammation that underlies chronic lung diseases such as idiopathic pulmonary fibrosis (IPF). Interleukin 11 (IL11) is important for pulmonary fibroblast activation but the contribution of fibroblast‐specific IL11 activity to lung fibro‐inflammation is not known. To address this gap in knowledge, we generated mice with loxP‐flanked Il11ra1 and deleted the IL11 receptor in adult fibroblasts (CKO mice). In the bleomycin (BLM) model of lung fibrosis, CKO mice had reduced fibrosis, lesser fibroblast ERK activation, and diminished immune cell STAT3 phosphorylation. Following BLM injury, acute inflammation in CKO mice was similar to controls but chronic immune infiltrates and pro‐inflammatory gene activation, including NF‐kB phosphorylation, were notably reduced. Therapeutic prevention of IL11 activity with neutralizing antibodies mirrored the effects of genetic deletion of Il11ra1 in fibroblasts. These data reveal a new function for IL11 in pro‐inflammatory lung fibroblasts and highlight the important contribution of the stroma to inflammation in pulmonary disease.